The influence of sowing rates on winter barley infection by Pyrenophora teres Drechsler under conditions of Steppe of Ukraine - Tіtov, I. (Quarantine and plant protection, 2024)
Goal. To determine the optimal seeding rates of winter barley to reduce the development of reticular helminthosporiosis (Pyrenophora teres Drechsler). Methods. Observations of crops of zoned winter barley varieties were carried out during the period from germination to milky-wax ripeness. The development of plant damage by the pathogen was determined on a six-point scale, taking into account the percentage of the affected leaf area. The basis of the methodological research is: empirical (field sampling, measurement of the object of study), theoretical (hypothesis formulation and conclusions based on the results of research), mathematical. Results. The damage to plants by the pathogen Pyrenophora teres Drechsler depended on the seeding rate. It was found that with an increase in sowing density, the degree of disease development increases. During the years of research, the development of the disease when sowing winter barley with 5.5 million seeds/ha was 3.0% higher compared to the norm of 4.5 million seeds/ ha and 1.2% higher than at the norm of 3.5 million. The grain yield was 0.18 t/ha less than the norm of 4.5 million seeds/ha and 0.14 t/ha less than the norm of 3.5 million seeds/ha. It was proved that a decrease in the seeding rate led to a decrease in the weight of 1000 grains by an average of 0.6 g. At the same time, there was a decrease in yield by 0.22 t/ha compared to sowing 4.5 million seeds/ ha. Conclusions. It was found that the optimal seeding rate for winter barley in Odesa region is 4.5 million seeds per 1 ha. At reduced and increased seeding rates, the damage to plants by the pathogen Pyrenophora teres Drechsler increases by 1.9—3.1%, respectively. Such sowings lead to a decrease in grain yield by 0.22—0.30 t/ ha compared to the sown areas where 4.5 million/ha of grains were sown.